Efektivitas model pembelajaran problem-based learning berbantuan animasi berbasis powtoon terhadap hasil belajar ekonomi siswa - Fadlilatul Amri; Jarot Tri Bowo Santoso (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Low economics learning outcomes and the dominance of conventional teaching highlight the need for instructional innovation that promotes students’ cognitive engagement. This study aimed to evaluate the effectiveness of the Problem Based Learning (PBL) model integrated with Powtoon-based animated media in improving students’ understanding of scarcity. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. Using purposive sampling, one class was assigned as the experimental group receiving PBL assisted by Powtoon, while another served as the control group with conventional instruction. Data were collected through a validated and reliable multiple-choice test. Prior to hypothesis testing, prerequisite analyses were conducted, followed by an independent sample t-test, while learning improvement was measured using the N-Gain score. The results indicated that the PBL-Powtoon integration significantly enhanced students’ learning outcomes and proved more effective than conventional methods. The improvement was categorized as high, particularly in students’ abilities to understand, analyze, and evaluate economic concepts. Overall, integrating problem-based learning with digital animated media constitutes an effective and innovative strategy to improve the quality of economics learning at the senior high school level.